1998
DOI: 10.1046/j.1471-4159.1998.71020471.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Translin and Trax as Components of the GS1 Strand‐Specific DNA Binding Complex Enriched in Brain

Abstract: In previous gel-shift assays, we identified a protein complex, referred to as GS1, that binds in a sequence-specific manner to single-stranded DNA and is highly enriched in brain. As an initial step in clarifying the function of this complex, we have undertaken studies aimed at defining its protein components. In particular, we focused on identifying two protein bands that were covalently labeled when the GS1 -DNA complex was subjected to UV irradiation to induce cross-linking between the radiolabeled probe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…The gel band corresponding to p35 was in-gel digested, treated as described under Materials and Methods and submitted to nanoelectrospray MS and MS/MS spectra on a Qtof mass spectrometer. From the recorded MS/MS mass spectra four partial sequences were found: XXF NCBInr data banks search revealed a high degree of homology with human, rat and chicken Trax, a previous described Translin-associated protein which has been suggested to be involved in the active nuclear transport of Translin (22,23,25) (Fig. 3C).…”
Section: Identification Of P35-x-translin Interacting Protein Asmentioning
confidence: 99%
See 1 more Smart Citation
“…The gel band corresponding to p35 was in-gel digested, treated as described under Materials and Methods and submitted to nanoelectrospray MS and MS/MS spectra on a Qtof mass spectrometer. From the recorded MS/MS mass spectra four partial sequences were found: XXF NCBInr data banks search revealed a high degree of homology with human, rat and chicken Trax, a previous described Translin-associated protein which has been suggested to be involved in the active nuclear transport of Translin (22,23,25) (Fig. 3C).…”
Section: Identification Of P35-x-translin Interacting Protein Asmentioning
confidence: 99%
“…Native form of Translin has been described as a ring-shaped structure with an assembly of eight subunits of 27 kDa monomer whose molecular mass is approximately 220 kDa (21). Moreover, several studies have shown that TB-RBP/Translin can interact with different proteins such as Trax, ␥-Actin, and the transitional endoplasmic reticulum ATPase (22)(23)(24)(25). To investigate if X-translin is present in metaphase II-arrested oocytes in association with other proteins, we have developed a gel filtration analysis.…”
Section: X-translin Is Present As a Complexed Protein In Xeno-mentioning
confidence: 99%
“…Sequence analysis in a meiotic recombination hot spot region of human chromosome 16 shows TB-RBP/Translin binding sequences near the breakpoint (7). TB-RBP/Translin has also been proposed to act as a single-stranded DNA-binding transcription factor, which activates early response gene expression in the brain (8). TB-RBP/Translin also functions as a RNA-binding protein mediating intracellular and intercellular mRNA transport (9,10).…”
mentioning
confidence: 99%
“…Both have putative leucine zipper domains at the C terminus of TB-RBP and in the mid-region of Trax (3,7). Interaction between TB-RBP and Trax has been demonstrated by coimmunoprecipitation (19) and in the yeast two-hybrid assay (7,8). Yeast two-hybrid and in vitro binding studies indicate that TB-RBP dimers are the minimum unit needed for DNA or RNA binding (20).…”
mentioning
confidence: 99%
“…The TRAX protein contains bipartite nuclear targeting sequences in its N-terminal region (Aoki et al 1997a), suggesting a possible role in the selective nuclear transport of Translin protein lacking any nuclear targeting motifs. It has been reported that TRAX and Translin associate in vivo as components of the NS1 strand-specific DNA binding complex enriched in brain (Taira et al 1998). Because Translin was found as a homopolymer in lymphoid cells, these results raise the possibility that Translin forms heteropolymers with TRAX in the central nervous system and regulates cellular functions, reminiscent of observations with Bcl-2-Bax (Oltvai et al 1993) or Myc-Max interactions (Blackwood and Eisenman 1991).…”
Section: Introductionmentioning
confidence: 62%